2023
DOI: 10.1177/17455057231166286
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards cervical cancer prevention among women in Khartoum state, Sudan

Abstract: Background: Cervical cancer is considered the third leading cause of death among women worldwide, and human papillomavirus was identified as a major causative agent for developing cervical cancer. Objectives: This study aimed to assess the knowledge and attitudes towards cervical cancer prevention among women in Khartoum state, Sudan. Design: A community-based cross-sectional study implemented in Khartoum state, Sudan, from 1 August 2020 to 1 September 2020. Methods: We conducted a descriptive cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The majority of the respondents (88%) were married, (96%) had formal education, (57%) were unemployed, (57%) had no income and a large number (83%) were Christians. These demographic characteristics have a bearing on one's knowledge and screening practices on cervical cancer as reported by Rimande-Joel et al, ( 2019) & Siddig et al, (2023). Participants' age, educational status, marital status, monthly income, religion, and knowledge were associated factors for cervical cancer screening practice; the main reason they did not get screened was that they felt healthy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The majority of the respondents (88%) were married, (96%) had formal education, (57%) were unemployed, (57%) had no income and a large number (83%) were Christians. These demographic characteristics have a bearing on one's knowledge and screening practices on cervical cancer as reported by Rimande-Joel et al, ( 2019) & Siddig et al, (2023). Participants' age, educational status, marital status, monthly income, religion, and knowledge were associated factors for cervical cancer screening practice; the main reason they did not get screened was that they felt healthy.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, only 13.22% had undergone Cervical Cancer screening. Studies by Rimande-Joel et al, ( 2019) & Siddig et al, (2023) in Nigeria and Sudan respectively revealed that the participant's knowledge and attitudes levels are mainly driven by their occupation, age educational level, family income, religion, and marital status altogether. However, knowledge about cervical cancer did not translate to right belief and good practice.…”
Section: Introductionmentioning
confidence: 99%